Bilateral leg extension power and fat-free mass in young oarsmen - Yoshiga, C. C.; Higuchi, M. (Journal of Sports Sciences, 2003)
We evaluated the impact of bilateral leg extension power and fat-free mass on 2000 m rowing ergometer performance in 332 young oarsmen (age 21+/-2 years, height 1.76+/-0.05 m, body mass 62+/-6 kg; mean+/-s). The 2000 m rowing performance time was correlated with height (1.62-1.93 m; R2=0.23, P<0.001), body mass (53-95 kg; R2=0.53, P<0.001), fat-free mass (47-82 kg; R2=0.58, P<0.001) and bilateral leg extension power (1202-3302 W; R2=0.38, P<0.001). Multiple regression analysis selected fat-free mass and bilateral leg extension power as regressor variables. Fat-free mass explained 58% of the variability in rowing performance and the inclusion of bilateral leg extension power improved the power of prediction by 5%. The results suggest that rowing involves almost every muscle in the body and that bilateral leg extension power is very important during this activity.